Functional Outcome of Extended Curettage and Reconstruction using Sandwich Technique for Giant Cell Tumor around Knee - Kevin Jose; Joe Joseph Cherian; Jerin Jeevo; Anoop Pilar; Rinju Krishnan; Mevin Mathew Nedumparambil (Journal of Orthopaedic Case Reports)
Introduction: Giant cell tumors (GCT) are benign yet locally aggressive neoplasms. The primary objectives of treatment are to entirely eliminate the tumor, rebuild the defect, and restore limb functionality. Numerous surgical treatment options have been proposed, ranging from more drastic interventions, such as en bloc excision, to less invasive techniques such as curettage or curettage combined with bone grafting. Limited research addresses the functional outcomes following treatment for giant cell tumors, despite the abundance of publications focusing on cure rates, recurrence, and other surgical considerations of the condition. Case Report: Individuals aged 20–40 are typically the ones affected with GCT. Patients typically exhibit pain during rest or sleep, and in certain instances, may also experience pathologic fractures. All patients were clinically evaluated, plain X-ray of the knee, chest X-ray, computed tomography , and magnetic resonance imaging were taken before the procedure. In all patients a pre-operative, biopsy was performed to determine the tumor’s histological grade and to confirm the diagnosis. Conclusion: The sandwich technique is an appropriate reconstructive procedure for GCT around the knee joint, involving the use of polymethylmethacrylate to occupy the residual cavity post-curettage, the placement of a structural allograft in the subchondral region, and the application of a gel form in the intervening space. It also has less complications, favorable survival rates, and positive functional outcomes. This approach preserves the advantages of cementing, mitigates potential complications, and restores the subchondral bone stock. None of our patients experienced any collapse of the joint, recurrences, immunological complications. All of them also had good functional status of the limb after 1 year. Thus, based on our good findings, we advocate this technique for joint salvage in GCTs around the knee.